Significance of G Protein-Coupled Estrogen Receptor in the Pathophysiology of Irritable Bowel Syndrome, Inflammatory Bowel Diseases and Colorectal Cancer - Jacenik, Damian; Krajewska, Wanda M. (Frontiers in Endocrinology, 2020)
The regulatory role of estrogens and nuclear estrogen receptors, i.e. estrogen receptor α and β has been reported in gastrointestinal diseases. However, the contribution of G protein-coupled estrogen receptor, the membrane-bound estrogen receptor, is still poorly understood. Unlike nuclear estrogen receptors, which are responsible for the genomic activity of estrogens, the G protein-coupled estrogen receptor affects the “rapid” non-genomic activity of estrogens, leading to modulation of many signaling pathways and ultimately changing gene expression. Recently, the crucial role of G protein-coupled estrogen receptor in intestinal pathogenesis has been documented. It has been shown that the G protein-coupled estrogen receptor can modulate the progression of irritable bowel syndrome, inflammatory bowel diseases such as Crohn’s disease and ulcerative colitis as well as colorectal cancer. The G protein-coupled estrogen receptor appears to be a potent factor regulating abdominal sensitivity and pain, intestinal peristalsis, colitis development, proliferation and migration potential of colorectal cancer cells, and seems to be a useful target in gastrointestinal diseases. In this review, we present the current state of knowledge about the contribution of the G protein-coupled estrogen receptor to irritable bowel syndrome, inflammatory bowel diseases and colorectal cancer.